2001
DOI: 10.1046/j.1439-0426.2001.00234.x
|View full text |Cite
|
Sign up to set email alerts
|

A fixed allele at microsatellite locus LS-39 exhibiting species-specificity for the black caviar producer Acipenser stellatus

Abstract: The sturgeon microsatellite LS-39 was ampli®ed across 10 dierent species of Acipenserinae and exhibited the potential to identify the black caviar producer Acipenser stellatus on a genomic DNA level. This was because of a ®xed allele of 111 bp, which was absent in the other species which were investigated. Concerning the source of sturgeon species, LS-39 is the ®rst nuclear marker described to examine black caviar. Furthermore, new light is shed on the controversial ploidy state of sturgeons. The present autho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 20 publications
0
21
0
1
Order By: Relevance
“…We considered individuals with three to four alleles per locus to be polyploid. A number of individuals and genotypes only had diploid microsatellite phenotypes (i.e., a maximum of two alleles per locus) and were subjected to an allele dosage analysis (Jenneckens et al 2001) to indicate whether they were diploid or polyploid. The basic assumption behind an allele dosage approach is that within a single PCR, alleles of the same locus are amplified quantitatively in relation to the copy number in which they occur in the nucleus of each cell, for example, when only two alleles are present (say, alleles A and B).…”
Section: Methodsmentioning
confidence: 99%
“…We considered individuals with three to four alleles per locus to be polyploid. A number of individuals and genotypes only had diploid microsatellite phenotypes (i.e., a maximum of two alleles per locus) and were subjected to an allele dosage analysis (Jenneckens et al 2001) to indicate whether they were diploid or polyploid. The basic assumption behind an allele dosage approach is that within a single PCR, alleles of the same locus are amplified quantitatively in relation to the copy number in which they occur in the nucleus of each cell, for example, when only two alleles are present (say, alleles A and B).…”
Section: Methodsmentioning
confidence: 99%
“…The number of SNPs required for correct assignment of market place fish to full sib families on a single farm was up to 400, to multiplier individuals (parents) it was 74 and to nucleus individuals, was 200. SNPs have been used for species identification of food products as tuna (Kitaoka et al, 2008) and food product origin, including sturgeon caviar origin (Jenneckens et al, 2001;Ogden et al, 2013).…”
Section: Traceability Of Aquaculture Productionmentioning
confidence: 99%
“…For instance, the genotype ABBC produces the microsatellite phenotype ABC, and cannot be reliably differentiated from genotypes AABC or ABCC. Jenneckens et al (2001) suggested to estimate the number of allele copies on the basis of peak heights and areas in the electropherograms as exemplified by the microsatellite locus LS-39 in the Siberian sturgeon Acipenser baerii. However, this approach seems not to be fully reliable: Congiu et al (2011) found that the four peaks of a complete heterozygous genotype did not always show the expected same height in Adriatic sturgeon, and the same discrepancy was observed in the present study of Russian sturgeon (data not shown).…”
Section: Discussionmentioning
confidence: 99%